(untitled) (Conference Zone, 2022)
Craniovertebral junction (CVJ) pathology is a defect in the occipital bone, foramen magnum, or the first two cervical vertebrae, resulting in decreased space for the lower brainstem and cervical spinal cord. One of the important components in the treatment of patients with CVP is restorative treatment both after surgical treatment and in cases where surgical treatment is not indicated [Safin Sh.M., 2019].